Use of tongue blades as a mouth orthosis for post-burn oral contractures. Issue 4 (October 2021) - Ayaz, Mehdi; Zohreie, Mohammad Rahim
Abstract: Introduction: With limited resources for rehabilitation, burn therapists throughout the world rely on local resources, professional creativity and community relationships to create solutions to help their patients recover. The demands of helping a burn survivor achieve an optimal outcome drive the burn therapist to create tools and strategies that effectively solve common problems after burn injury. Methods: The International Society for Burn Injury (ISBI) invited burn therapists from around the world to describe the innovations that they have created to solve burn rehabilitation problems. The submissions were provided through an online form and inclusion of photographs was encouraged. Each submission was reviewed in a blinded manner by an expert panel of three independent rehabilitation therapists from the ISBI Rehabilitation Committee. The submissions were reviewed for originality, utility, quality and safety, then edited and compiled to be shared and disseminated throughout the world. Results: A total of 77 innovations were submitted for review. 71 were accepted for publication (92%) and given the opportunity to publish in Burns Open . Clinicians from 15 countries submitted innovations. The innovations were categorized as: Orthosis, Scar Management, Techniques, Activities of Daily Living Devices, Educational Tools and Prosthesis. Nineteen submissions were translated from Spanish to English. Discussion: Creative and innovative ideas using local resources are turned into patient solutions by experienced burn therapists around the world. However, because such innovations don't reach widespread investigation or production, the ideas remain in a silo in the local area when they could be of use to therapists in other cultures. This project resulted in a book of "Innovative Solutions in Burn Rehabilitation from Around the World, " that was printed and is now available as this Special Edition in Burns Open . Future work would include expanding on the book with more innovative solutions and translating it into multiple languages to improve access and usability throughout the world.